Determination of environmental conditions for the conservation of dehydrated cocoa beans (Theobroma cacao L) during storage. (Revista Sistemas de Producción Agroecológicos, 2020)
Cocoa (Theobroma cacao L.) is one of the representative crops of the department of Meta (Colombia), whose grains are used in the chocolate industry. Storage is a point of control since deterioration phenomena can occur that affect its quality. During this period, variations in temperature and relative humidity occur, causing losses in the physicochemical and organoleptic properties of the grains due to their hygroscopic capacity, facilitating the growth of fungi. Therefore, in this work it was tried to determine conditions of temperature and relative humidity in order to seek to prolong the useful life of dehydrated cocoa beans during their storage period. To do this, adsorption isotherms were constructed at temperatures of 25, 30 and 35°C for the range of αw between 0.146 and 0.891. Where type II isotherms were obtained by having an "S" shape or by being a sigmoid type. These were adjusted to mathematical models commonly applied in food. The fit of the models was evaluated with that which present a more acceptable mean square error root (RMSE) and a correlation coefficient (R2) close to 1. Based on which, it was observed that the model proposed by Smith presented the best fit of the experimental data. The results obtained allowed us to propose that at conditions of relative humidity greater than 51.4% and equal to or lower than 58.9% and at a temperature of 25°C, the shelf life of dehydrated cocoa beans would be maintained maintaining quality standards during the storage process.
Keywords: sorption isotherms; water activity; mathematical models; relative humidity; temperature; cocoa FEAR-5 clone